2013
DOI: 10.1038/ncomms3142
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of vitamin B metabolites by mucosal-associated invariant T cells

Abstract: The mucosal-associated invariant T-cell antigen receptor (MAIT TCR) recognizes MR1 presenting vitamin B metabolites. Here we describe the structures of a human MAIT TCR in complex with human MR1 presenting a non-stimulatory ligand derived from folic acid and an agonist ligand derived from a riboflavin metabolite. For both vitamin B antigens, the MAIT TCR docks in a conserved manner above MR1, thus acting as an innate-like pattern recognition receptor. The invariant MAIT TCR a-chain usage is attributable to MR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
354
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(392 citation statements)
references
References 39 publications
25
354
1
Order By: Relevance
“…We did not find amino acid motifs within the CDR3b, although it does contact the MR1-a1 chain 31,32 . The absence of conserved motifs is consistent with the known absence of effects on antigen reactivity on single amino acid substitutions in the CDR3b chain of MAIT TCR 30,46 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We did not find amino acid motifs within the CDR3b, although it does contact the MR1-a1 chain 31,32 . The absence of conserved motifs is consistent with the known absence of effects on antigen reactivity on single amino acid substitutions in the CDR3b chain of MAIT TCR 30,46 .…”
Section: Discussionmentioning
confidence: 92%
“…The co-crystal of the TCR of MAIT cells and MR1 showed that CDR3b residues form van der Waals interactions with the MR1 a1 helix, thereby contributing to the overall interaction between the two proteins 31,32 . The preferential length of MAIT CDR3b sequences might contribute to optimal recognition of MR1-antigen complexes.…”
Section: Cdr3b Length Distribution Differs In Mait and Non-mait Cellsmentioning
confidence: 99%
“…The remarkable evolutionary conservation of this system (25) implies an essential role in host defense, which has yet to be defined. It has recently been shown that MAIT cells recognize small molecule derivatives of highly conserved biosynthetic pathways of riboflavin and folic acid metabolism in bacteria, mycobacteria, and yeasts (26,27) presented on the nonpolymorphic class 1b antigen presenting molecule major histocompatibility complex (MHC)-related protein 1 (MR1) (28,29). Because of their propensity for intracellular invasion of epithelia and macrophages (6), and because they express this riboflavin pathway (30), NTHi is a likely target of MAIT-cell immunity.…”
Section: Cd161mentioning
confidence: 99%
“…Recent work conducted by Ló pez-Sagaseta et al [67] and Patel et al [68] revealed interesting structural, biophysical and biochemical aspects of ligand binding to MR1 and recognition of this complex by MAIT cells. Furthermore, the studies reveal how MAIT cells exert their effector functions via CDR3b loop diversity and alternate Vb gene usage.…”
Section: Mr1 Ligands Ligand Binding and Mr1-ligand Complex Binding mentioning
confidence: 99%